Common Fixed Points in Generalized Metric Spaces with a Graph - Karim Chaira; Mustapha Kabil; Abdessamad Kamouss (Journal of Mathematics)
The aim of this paper is to prove the existence and uniqueness of points of coincidence and common fixed points for a pair of self-mappings defined on generalized metric spaces with a graph. Our results improve and extend several recent results of metric fixed point theory.